A centripetal porous aerogel and its preparation method and application
Through centripetal freezing method and thermochemical vapor deposition technology, aerogel materials with centripetal porous structure were prepared, which solved the problem of insufficient mechanical properties of existing aerogel materials and achieved efficient sound absorption, heat insulation and oil and water Separation effect.
Patent Information
- Application Number
- CN202410326476.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-03-21
AI Technical Summary
The existing aerogel materials have relatively brittle properties and lack excellent mechanical rebound properties, which limits their application range.
Centripe porous aerogels are prepared by centripetal freezing method, and the lipidation reaction of bacterial cellulose and polycarboxylic acids and thermochemical vapor deposition of polysiloxane are formed to form a material with a centripetal porous structure.
A centripetal porous aerogel with lightweight, high porosity, excellent mechanical rebound properties and negative Poisson's ratio characteristics has been obtained. It is suitable for sound absorption, heat insulation and oil-water separation.
Smart Images

Figure CN118126403B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a centripetal porous aerogel and a preparation method and application thereof, belonging to the technical field of porous aerogel preparation. Background Art
[0002] Aerogel materials, as the lightest solid material reported, are attracting widespread attention. At the same time, due to their unique properties such as low density, high porosity, high specific surface area, and low thermal conductivity, aerogels can be applied to many fields such as adsorption, thermal regulation, sensors, and biomedicine.
[0003] However, current aerogels are often brittle and lack excellent mechanical resilience, which often limits their scope of application. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a centripetal porous aerogel. The centripetal porous aerogel provided by the present invention has the characteristics of light weight, high porosity, excellent mechanical resilience and negative Poisson's ratio.
[0005] The second object of the present invention is to provide a method for preparing a centripetal porous aerogel. The preparation method of the present invention freezes the raw material by a centripetal freezing method under a unidirectional temperature field, adjusts the content of bacterial cellulose in the raw material, controls the thickness of the porous aerogel, and obtains a centripetal porous aerogel with excellent mechanical rebound performance and negative Poisson's ratio.
[0006] The third object of the present invention is to provide an application of a centripetal porous aerogel. The centripetal porous aerogel provided by the present invention has a wide range of uses. When used as a sound-absorbing material, it can achieve efficient sound absorption in high, medium and low frequency bands. When used as a heat-insulating material, it can effectively isolate high temperatures and protect the health of personnel. When used as an oil-water separation material, it can efficiently adsorb a variety of oils and organic reagents in the water body.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The invention discloses a centripetal porous aerogel, which comprises a polymer matrix framework and polysiloxane deposited on the polymer matrix framework. The polymer matrix framework is obtained by lipidation reaction of bacterial cellulose and polycarboxylic acid. The centripetal porous aerogel has a centripetal porous structure.
[0009] The centripetal porous aerogel provided by the present invention has a centripetal porous structure, and its pore structure is all centripetally oriented, that is, the pores of the centripetal porous aerogel are directional and arranged from the bottom and surrounding of the centripetal porous aerogel to the top of the central axis of the centripetal porous aerogel. In the centripetal porous aerogel, bacterial cellulose acts as a polymer matrix framework in the system and provides an intertwined network structure inside the material. The addition of polycarboxylic acid can undergo esterification and cross-linking reactions with the hydroxyl groups on cellulose, effectively improving the mechanical properties of the material and preventing collapse during material production and application. In addition, the polysiloxane deposited on the polymer matrix framework can further enhance the mechanical properties of the material and give the material excellent resilience, and the presence of non-polar methyl groups gives the material excellent hydrophobicity.
[0010] In addition, since the centripetal porous aerogel has a centripetal porous structure, it can further give the material low density, negative Poisson's ratio characteristics, excellent sound absorption and noise reduction performance, excellent thermal insulation performance and efficient oil-water separation ability. First, the centripetal porous structure means that the centripetal porous aerogel of the present invention obtains abundant porous channels, which greatly improves the porosity of the material, can effectively reduce the density of the material, and give the material extremely light properties. At the same time, when the centripetal porous aerogel is subjected to longitudinal compression, the centripetal channels will shrink toward the central axis, giving the material negative Poisson's ratio characteristics; in addition, the centripetal porous aerogel will have a complex channel structure, which prolongs the loss path of noise under limited sample thickness and improves the sound absorption and noise reduction performance; at the same time, the centripetal porous microstructure effectively prevents air convection, reduces thermal radiation and heat conduction, and improves the thermal protection performance of the material; finally, the continuous and abundant porous structure in the centripetal porous aerogel can efficiently absorb oil and organic hazards in water, and realize effective oil-water separation function.
[0011] In a preferred embodiment, the microstructure of the bacterial cellulose is in the form of filaments.
[0012] In a preferred embodiment, the polycarboxylic acid is at least one selected from citric acid, 1,2,3,4-butanetetracarboxylic acid, maleic acid, and itaconic acid.
[0013] In a preferred embodiment, the content of the polycarboxylic acid is 5-20% of the mass of the bacterial cellulose.
[0014] In a preferred embodiment, the polysiloxane on the polymer matrix frame is obtained by thermal chemical vapor deposition of 0.1 to 1 mL of liquid methyltrimethoxysilane.
[0015] The inventors found that in the porous sound-absorbing and heat-insulating aerogel, the amount of each substance is controlled within the above range, and the final porous sound-absorbing and heat-insulating aerogel has the best performance. If the solid content of bacterial cellulose is too low, the mechanical properties of the material are poor, and the sound absorption and heat insulation properties are also limited. If the solid content of bacterial cellulose is too high, the density of the material is increased, so that the material does not have the characteristics of lightness. In addition, if the amount of 1,2,3,4-butanetetracarboxylic acid and methyltrimethoxysilane used is too high or too low, it will have an adverse effect on the mechanical properties of the material.
[0016] In a preferred embodiment, the thickness of the centripetal porous aerogel is 5 to 30 mm, preferably 5 to 20 mm.
[0017] The inventors found that when the thickness of the centripetal porous aerogel is 5 to 30 mm, it can be used as a sound absorbing material or a heat insulating material, and when the thickness of the centripetal porous aerogel is 5 to 20 mm, it can be used as any one of a sound absorbing material, a heat insulating material, and an oil-water separation material. If the centripetal porous aerogel is too thin, effective sound absorption performance cannot be guaranteed. At the same time, thinner aerogels cannot fully absorb oil and organic hazards in water. If the centripetal porous aerogel exceeds 20 mm, the buoyancy is often large, making it difficult to absorb oil and organic hazards that sink to the bottom of the water. If it exceeds 30 mm, the overall weight of the sample will increase, limiting various applications.
[0018] The invention discloses a method for preparing a centripetal porous aerogel. The method comprises the following steps: adding polycarboxylic acid and a catalyst to a bacterial cellulose dispersion liquid B and mixing the mixture uniformly to obtain a slurry. The slurry is poured into a mold and placed in a unidirectional temperature field for centripetal freezing. The slurry is then freeze-dried and heat-treated to obtain a polymer matrix frame. Finally, methyltrimethoxysilane is used to perform thermochemical vapor deposition on the polymer matrix frame to obtain the centripetal porous aerogel. The mold has an open top and is covered with copper tape on all sides and the bottom.
[0019] The preparation method provided by the present invention utilizes polycarboxylic acid and bacterial cellulose to undergo lipidation reaction during heat treatment to effectively improve the mechanical properties of the material, and utilizes methyltrimethoxysilane to perform a thermal chemical vapor deposition reaction on the sample, which can further enhance the mechanical properties of the material and give the material excellent resilience. When centripetal freezing is performed in a unidirectional temperature field, copper tape is covered on all sides and the bottom surface. When the bottom surface of the mold contacts a cold source, the covered copper tape can cause a centripetal temperature field to be generated around the mold, so that the organic matter in the slurry will be pushed to the solid-liquid interface by ice crystals, thereby generating the desired centripetal porous structure.
[0020] The inventors have discovered that when centripetal freezing is performed in a unidirectional temperature field, only when the bottom surface and surrounding surfaces of the mold are wrapped with copper tape at the same time, the pore structure in the sample is a centripetal structure in which the pores are arranged from the bottom end and surrounding surfaces of the sample to the top of the central axis of the sample. This is because in the present invention, a cold source is only generated at the surface wrapped with copper tape, and the growth of ice crystals is achieved. That is, if copper tape is not wrapped around the surrounding and bottom surfaces, centripetal porosity cannot be generated. If copper tape is only wrapped on one surface of the bottom surface of the mold, the pores generated in the sample will be directional through holes from bottom to top; if copper tape is only wrapped on the bottom surface of the mold and any three surfaces around it, the pores in the sample will grow from the bottom surface and the three surrounding surfaces, and the centripetal condition is not met.
[0021] In a preferred embodiment, bacterial cellulose dispersion A is diluted with a solvent to obtain bacterial cellulose dispersion B.
[0022] In a preferred embodiment, in the bacterial cellulose dispersion A, the mass fraction of bacterial cellulose is 0.65-1%.
[0023] In a preferred embodiment, the solvent is selected from at least one of deionized water and anhydrous ethanol.
[0024] In a preferred embodiment, the polycarboxylic acid is at least one selected from citric acid, 1,2,3,4-butanetetracarboxylic acid, maleic acid, and itaconic acid.
[0025] In a preferred embodiment, the amount of the polycarboxylic acid added is 5-20% of the mass of the bacterial cellulose.
[0026] In a preferred embodiment, the catalyst is selected from at least one of sodium hypophosphite and potassium hypophosphite.
[0027] In a preferred embodiment, the catalyst is added in an amount of 30-60% of the mass of the polycarboxylic acid.
[0028] In a preferred embodiment, during the centripetal freezing, the cold end of the directional freezing temperature field is set to -196 to -20°C, the hot end is room temperature, and the centripetal freezing time is 10 to 60 minutes. Conical ice crystals will be generated near the cold source. Depending on the different copper tape wrapping, the cold source can be guided to the required surface of the mold. At this time, the organic matter in the slurry will be pushed to the solid-liquid interface by the ice crystals, and the required centripetal porous structure will be generated.
[0029] In a preferred embodiment, the freeze drying temperature is -60 to 0°C, the vacuum degree is 1 to 100 Pa, and the freeze drying time is 24 to 72 hours. During the freeze drying process, the material will be placed in a vacuum environment, and the ice in the system will be removed in the form of sublimation.
[0030] In a preferred embodiment, the heat treatment temperature is 150-190° C. and the heat treatment time is 3-10 min. Through the heat treatment, an esterification reaction is carried out, and the carboxyl groups of the polycarboxylic acid will chemically crosslink with the hydroxyl groups in the cellulose. The esterification reaction will improve the mechanical stability of the sample.
[0031] In a preferred embodiment, the temperature of the thermal chemical vapor deposition is 60 to 90° C., and the time of the thermal chemical vapor deposition is 20 to 200 minutes. The thermal chemical vapor deposition can impart hydrophobic properties and excellent resilience to the material.
[0032] The present invention also provides an application of the centripetal porous aerogel, wherein the porous sound-absorbing and heat-insulating aerogel is used as at least one of a sound-absorbing material, a heat-insulating material, and an oil-water separation material.
[0033] Beneficial Effects
[0034] The centripetal porous aerogel provided by the present invention has a centripetal porous structure, and its pore structure is centripetally oriented, that is, the pores of the centripetal porous aerogel are oriented from the bottom and surrounding of the centripetal porous aerogel to the top of the central axis of the centripetal porous aerogel, and in the centripetal porous aerogel, bacterial cellulose acts as a polymer matrix framework in the system and provides an intertwined mesh structure inside the material. The addition of polycarboxylic acid can react with the hydroxyl groups on cellulose to undergo esterification and cross-linking, effectively improving the mechanical properties of the material and preventing collapse during the production and application of the material. In addition, the polysiloxane deposited on the polymer matrix framework can further enhance the mechanical properties of the material and give the material excellent resilience, and the presence of non-polar methyl groups gives the material excellent hydrophobicity.
[0035] In addition, due to the centripetal porous structure of the centripetal porous aerogel, the material can be further endowed with low density, negative Poisson's ratio characteristics, excellent sound absorption and noise reduction performance, excellent thermal insulation performance and efficient oil-water separation ability. First, the centripetal porous structure means that the centripetal porous aerogel of the present invention obtains abundant porous channels, which greatly improves the porosity of the material, can effectively reduce the density of the material, and endows the material with extremely light properties. At the same time, when the centripetal porous aerogel is subjected to longitudinal compression, the centripetal channels will shrink toward the central axis, giving the material negative Poisson's ratio characteristics; in addition, the centripetal porous aerogel will have a complex channel structure, which prolongs the loss path of noise under limited sample thickness and improves the sound absorption and noise reduction performance; at the same time, the centripetal porous microstructure effectively prevents air convection, reduces thermal radiation and heat conduction, and improves the thermal protection performance of the material; finally, the continuous and abundant porous structure in the centripetal porous aerogel can efficiently absorb oil and organic hazards in water, and realize effective oil-water separation function.
[0036] The preparation method provided by the present invention utilizes polycarboxylic acid and bacterial cellulose to undergo lipidation reaction during heat treatment to effectively improve the mechanical properties of the material, and utilizes methyltrimethoxysilane to perform a thermal chemical vapor deposition reaction on the sample, which can further enhance the mechanical properties of the material and give the material excellent resilience. When centripetal freezing is performed in a unidirectional temperature field, copper tape is covered on the surroundings and bottom surface. When the bottom surface of the mold contacts a cold source, the covered copper tape can cause a centripetal temperature field to be generated around the mold, so that the organic matter in the slurry will be pushed to the solid-liquid interface by ice crystals, thereby generating the desired centripetal porous structure.
[0037] The porosity of the centripetal porous aerogel provided by the present invention is 99.6%, and the density is only 2.58 mg / cm 3 , and has an extremely low room temperature thermal conductivity of 24.3mW / (m·K), which is lower than the thermal conductivity of air under the same conditions. In the preferred embodiment, a 20mm thick sample is roasted on a heating table at 150°C for 10 minutes, and the upper surface temperature is only 47.8°C, showing excellent thermal insulation performance. In the preferred embodiment, the 30mm centripetal porous aerogel exhibits excellent sound absorption performance, maintaining a sound absorption coefficient greater than 0.5 at frequencies of 600Hz and higher. In addition, the centripetal porous aerogel provided by the present invention can still rebound efficiently after bearing an axial compression load of 80%, and has a negative Poisson's ratio of -0.6. In the preferred embodiment, the centripetal porous aerogel can achieve an adsorption capacity of 215g / g for diesel and an adsorption capacity of up to 230g / g for tetrahydrofuran. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the mold design drawing used in Example 1.
[0039] Figure 2 This is a cross-sectional SEM image of the centripetal porous aerogel prepared by the method in Example 1.
[0040] Figure 3 This is a curve showing how the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 1 varies with frequency band.
[0041] Figure 4 This is the compressive stress-strain diagram of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1.
[0042] Figure 5 This is the compression-rebound diagram of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1.
[0043] Figure 6 Schematic diagram of the negative Poisson's ratio of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1.
[0044] Figure 7Schematic diagram of the water contact angle of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1.
[0045] Figure 8 This is a graph showing the oil absorption test results of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1.
[0046] Fig. 9 This is a curve showing how the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 2 varies with frequency band.
[0047] Fig.10 This is the compressive stress-strain diagram prepared by the method in Example 2.
[0048] Fig.11 This is a graph showing the oil-water separation test results of the aerogel prepared by the method in Example 3.
[0049] Fig.12 This is an infrared thermal image of the centripetal porous aerogel prepared by the method in Example 3.
[0050] Fig.13 This is the curve of the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 4 as a function of frequency band.
[0051] Fig.14 This is the SEM image of the oriented porous aerogel prepared by the method in Comparative Example 2.
[0052] Fig.15 This is a curve showing how the sound absorption coefficient of the oriented porous aerogel prepared by the method in Example 2 changes with frequency band.
[0053] Fig.16 This is a compression diagram of the directional porous sound-absorbing and heat-insulating aerogel prepared by the method in Example 3.
[0054] Fig.17 This is an infrared thermal image of the oriented porous aerogel prepared by the method in Comparative Example 3.
[0055] Fig.18 This is a photo of a material obtained in Comparative Example 4 with water droplets dyed with methyl orange. DETAILED DESCRIPTION
[0056] Example 1
[0057] Take 48.75g of 0.8wt% bacterial cellulose aqueous dispersion, add 146.25g of deionized water, 0.039g of 1,2,3,4-butanetetracarboxylic acid and 0.0195g of sodium hypophosphite, stir well, and pour the mixed slurry into a prefabricated 10mm high square mold for freeze casting. Figure 1This is the design drawing of the mold used in this embodiment. The top of the square silicone mold is open, and the surroundings and bottom are evenly covered with copper tape. When the bottom of the mold contacts the cold source, the covered copper tape can cause a centripetal temperature field to be generated around the mold. The bottom of the mold filled with slurry is placed on a hot and cold plate at -100°C and frozen for 40 minutes to obtain a white block frozen sample. Subsequently, the frozen sample is peeled off from the mold and placed at -50°C and freeze-dried for 72 hours under a vacuum of 10Pa to remove the ice in the sample by sublimation. The freeze-dried sample is placed in a beaker and placed in an oven at 170°C for 5 minutes for esterification. Subsequently, the sample is transferred to a stainless steel sealed reaction vessel, the sample is placed on the upper layer of the reaction vessel, 0.5mL of methyltrimethoxysilane is placed on the lower layer of the reaction vessel, and the reaction is carried out at 70°C for 30 minutes for thermal chemical vapor deposition to obtain a centripetal porous aerogel.
[0058] Table 1 shows the basic physical properties of the centripetal porous aerogel prepared by the method in Example 1. It can be seen that the porosity of the aerogel is as high as 99.6% and the density is only 2.58 mg / cm 3 Its thermal conductivity at room temperature is 24.3mW / (m·K), which is lower than the thermal conductivity of air at room temperature, 26.7mW / (m·K).
[0059] Table 1
[0060]
[0061] Figure 2 This is a cross-sectional SEM image of the centripetal porous aerogel prepared by the method in Example 1. The microscopic morphology shows that the pores inside the aerogel prepared in Example 1 all grow in a centripetal manner.
[0062] Figure 3 This is the curve of the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 1. It can be seen that the 10 mm thick sample has excellent sound absorption performance at high, medium and low frequencies, and maintains a sound absorption coefficient greater than 0.5 at frequencies of 2100 Hz and higher.
[0063] Figure 4 : is the compressive stress-strain diagram of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1. In the stress-strain diagram, the aerogel presents a loading-unloading hysteresis loop, which can achieve effective energy dissipation.
[0064] Figure 5 This is a compression-rebound diagram of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1. When the aerogel is subjected to axial strain loading, it can still rebound efficiently without macroscopic irreversible deformation.
[0065] Figure 6Schematic diagram of negative Poisson's ratio of negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1. When the aerogel is subjected to axial compression, it will shrink radially, showing a negative Poisson's ratio phenomenon.
[0066] Figure 7 Schematic diagram of water contact angle of negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1. The water contact angle of the aerogel is as high as 140°, which is an excellent hydrophobic material.
[0067] Figure 8 1 is a graph showing the oil absorption test results of the negative Poisson's ratio oil-water separation aerogel prepared by the method in Example 1. The aerogel can achieve efficient oil absorption capacity.
[0068] Example 2
[0069] The other preparation processes remained the same as in Example 1, except that the addition amount of 0.8 wt % bacterial cellulose aqueous dispersion in the slurry was 142.5 g, the addition amount of deionized water was 142.5 g, the addition amount of 1,2,3,4-butanetetracarboxylic acid was 0.114 g, and the addition amount of sodium hypophosphite was 0.057 g.
[0070] Table 2 shows the basic physical properties of the centripetal porous aerogel prepared by the method in Example 2. It can be seen that with the increase of cellulose solid content in the sample, the porosity of the aerogel slightly decreased to 99.4%, but still maintained a low density of 5.04 mg / cm 3 , its thermal conductivity at room temperature slightly increases to 26.5mW / (m·K).
[0071] Table 2
[0072]
[0073] Fig. 9 This is the curve of the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 2. It can be seen that the sound absorption performance of the 10 mm thick sample at medium and low frequencies is significantly improved compared with Example 1. At 2000 Hz, the sound absorption performance of Example 2 is improved from 0.48 in Example 1 to 0.80.
[0074] Fig.10 This is a compressive stress-strain diagram prepared by the method in Example 2. It can be seen that with the increase of the solid content of bacterial cellulose, the compressive strength of the aerogel in Example 2 increases significantly, and when the strain is 80%, the compressive stress reaches 20.2 kPa.
[0075] Example 3
[0076] The other preparation processes remain the same as those in Example 2, except that the uniformly mixed slurry is filled into a prefabricated mold with a height of 20 mm during freeze casting.
[0077] Fig.11 This is a diagram showing the oil-water separation test results of the aerogel prepared by the method in Example 3. It can be seen that the aerogel can quickly absorb diesel suspended on the water surface, showing a highly efficient oil-water separation capability.
[0078] Fig.12 This is an infrared thermal image of the centripetal porous aerogel prepared by the method in Example 3. A 20 mm thick sample was placed on a heating table at 150°C and the sample temperature was recorded using an infrared thermal imager. The top surface temperature of the sample was recorded 10 minutes later and was only 47.8°C.
[0079] Example 4
[0080] The other preparation processes remain the same as those in Example 2, except that the uniformly mixed slurry is filled into a prefabricated mold with a height of 30 mm during freeze casting.
[0081] Fig.13 This is the curve of the sound absorption coefficient of the centripetal porous aerogel prepared by the method in Example 4. It can be seen that the mid- and low-frequency sound absorption performance of the 30 mm high sample is significantly enhanced, and the sound absorption coefficient is greater than 0.5 at frequencies of 600 Hz and higher. At the same time, the sound absorption coefficient of the sample reaches 0.18 at 200 Hz and 0.84 at 1000 Hz, showing excellent mid- and low-frequency sound absorption performance.
[0082] Comparative Example 1
[0083] The other preparation processes were the same as those in Example 1, except that the slurry configuration was changed, and 1,2,3,4-butanetetracarboxylic acid and sodium hypophosphite were not added thereto. Also, after freeze drying, no thermal chemical vapor deposition reaction was performed.
[0084] The sample prepared in Comparative Example 1 does not have good mechanical properties. When subjected to external forces such as pressing and impact, its macroscopic structure and morphology will be irreversibly damaged, and the subsequent sound absorption and heat insulation applications cannot be guaranteed.
[0085] Comparative Example 2
[0086] The other preparation processes remain the same as in Example 1, only the design of the mold into which the slurry is poured during freeze casting is changed. In this comparative example, copper tape is not applied around and on the bottom of the silicone mold. During freeze casting, the slurry is directly poured into the silicone mold, and the bottom of the mold is placed on a hot and cold plate. Since the sample is affected by a unidirectional temperature field from bottom to top during freeze casting, the obtained sample is an oriented porous aerogel.
[0087] Fig.14 This is a SEM image of the directional porous sound-absorbing and heat-insulating aerogel prepared by the method in Comparative Example 2. The microscopic morphology shows that the pores inside the aerogel prepared in Comparative Example 2 grow in a unidirectional manner.
[0088] Fig.15 This is a curve of the sound absorption coefficient of the directional porous sound-absorbing and heat-insulating aerogel prepared by the method in Example 2. It can be seen that the 10 mm thick aerogel prepared by this method still has effective sound absorption performance, but the sound absorption coefficient in the medium and high frequency bands is significantly lower than that of the centripetal porous aerogel prepared in Example 1.
[0089] Comparative Example 3
[0090] The other preparation processes remain the same as those of Comparative Example 2, except that the uniformly mixed slurry is filled into a prefabricated mold with a height of 20 mm during freeze casting.
[0091] Fig.16 This is a compression diagram of the directional porous sound-absorbing and heat-insulating aerogel prepared by the method in Comparative Example 3. It can be seen that the aerogel prepared in Comparative Example 3 does not have the negative Poisson's ratio property.
[0092] Fig.17 This is an infrared thermal image of the directional porous sound-absorbing and heat-insulating aerogel prepared by the method in Example 3. A 20 mm thick sample was placed on a heating table at 150°C for baking, and the sample temperature was recorded using an infrared thermal imager. The top surface temperature of the sample was recorded after 10 minutes, which was 59.5°C. Compared with Example 3, the upper surface temperature of the sample in Example 3 increased by 11.7°C under the same baking conditions. This is because the prepared sample has interconnected directional holes from bottom to top, which significantly reduces the thermal insulation capacity of the sample.
[0093] Comparative Example 4
[0094] The other preparation processes remain the same as those in Example 1, except that the thermal chemical vapor deposition reaction is not performed after the esterification reaction is completed.
[0095] Fig.18 This is a physical picture of a water drop dyed with methyl orange being dropped onto the material obtained in Comparative Example 4. It can be seen that the material does not have hydrophobicity, and absorbs the water droplets the moment they touch the surface of the material, causing the structure to collapse, and subsequent applications cannot be guaranteed.
Claims
1. A method for preparing a centripetal porous aerogel, characterized in that: Adding polycarboxylic acid and a catalyst to bacterial cellulose dispersion B and mixing evenly to obtain a slurry, pouring the slurry into a mold, placing it in a unidirectional temperature field for centripetal freezing, then freeze-drying and heat-treating to obtain a polymer matrix framework, and finally using methyltrimethoxysilane to perform thermal chemical vapor deposition on the polymer matrix framework to obtain a centripetal porous aerogel, wherein the mold has an open top and is covered with copper tape on the sides and bottom; Adding a solvent to dilute the bacterial cellulose dispersion A to obtain a bacterial cellulose dispersion B; in the bacterial cellulose dispersion A, the mass fraction of the bacterial cellulose is 0.65-1%; The amount of the polycarboxylic acid added is 5-20% of the mass of the bacterial cellulose; The polysiloxane on the polymer matrix framework is obtained by thermal chemical vapor deposition of 0.1-1 mL of liquid methyltrimethoxysilane; During the centripetal freezing, the cold end of the directional freezing temperature field is set to -196~-20°C, the hot end is room temperature, and the centripetal freezing time is 10~60min; The centripetal porous aerogel comprises a polymer matrix framework and polysiloxane deposited on the polymer matrix framework, wherein the polymer matrix framework is obtained by lipidation reaction of bacterial cellulose and polycarboxylic acid, and the centripetal porous aerogel has a centripetal porous structure; The pores of the centripetal porous aerogel are arranged in a direction from the bottom end of the centripetal porous aerogel and the top end of the periphery toward the central axis of the centripetal porous aerogel; The thickness of the centripetal porous aerogel is 5-30 mm.
2. The method for preparing a centripetal porous aerogel according to claim 1, characterized in that: The solvent is selected from at least one of deionized water and anhydrous ethanol.
3. The method for preparing a centripetal porous aerogel according to claim 1, characterized in that: The polycarboxylic acid is selected from at least one of citric acid, 1,2,3,4-butanetetracarboxylic acid, maleic acid and itaconic acid.
4. The method for preparing a centripetal porous aerogel according to claim 1, characterized in that: The catalyst is selected from at least one of sodium hypophosphite and potassium hypophosphite; The catalyst is added at 30-60% of the mass of the polycarboxylic acid.
5. The method for preparing a centripetal porous aerogel according to claim 1, characterized in that: The freeze-drying temperature is -60~0°C, the vacuum degree is 1~100Pa, and the freeze-drying time is 24~72h.
6. The method for preparing a centripetal porous aerogel according to claim 1, characterized in that: The heat treatment temperature is 150-190°C and the heat treatment time is 3-10 minutes; The temperature of the thermal chemical vapor deposition is 60-90° C., and the time of the thermal chemical vapor deposition is 20-200 min.
7. Use of a centripetal porous aerogel prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The centripetal porous aerogel is used as at least one of a sound absorbing material, a heat insulating material, and an oil-water separation material.
Citation Information
Patent Citations
Preparation method and application of high-elasticity bacterial cellulose aerogel
CN115806694A
Graphene aerogel with stable structure and high elasticity and preparation method thereof
CN115893391A